ABA Suppresses Root Hair Growth via the OBP4 Transcriptional Regulator. Issue 3 (6th February 2017) - Rymen, Bart; Kawamura, Ayako; Schäfer, Sabine; Breuer, Christian; Iwase, Akira; Shibata, Michitaro; Ikeda, Miho; Mitsuda, Nobutaka; Koncz, Csaba; Ohme-Takagi, Masaru; Matsui, Minami; Sugimoto, Keiko
Abstract : The DOF transcription factor OBP4 suppresses root hair growth by down-regulating RSL2 expression in Arabidopsis. Abstract: Plants modify organ growth and tune morphogenesis in response to various endogenous and environmental cues. At the cellular level, organ growth is often adjusted by alterations in cell growth, but the molecular mechanisms underlying this control remain poorly understood. In this study, we identify the DNA BINDING WITH ONE FINGER (DOF)-type transcription regulator OBF BINDING PROTEIN4 (OBP4) as a repressor of cell growth. Ectopic expression of OBP4 in Arabidopsis ( Arabidopsis thaliana ) inhibits cell growth, resulting in severe dwarfism and the repression of genes involved in the regulation of water transport, root hair development, and stress responses. Among the basic helix-loop-helix transcription factors known to control root hair growth, OBP4 binds the ROOT HAIR DEFECTIVE6-LIKE2 ( RSL2 ) promoter to repress its expression. The accumulation of OBP4 proteins is detected in expanding root epidermal cells, and its expression level is increased by the application of abscisic acid (ABA ) at concentrations sufficient to inhibit root hair growth. ABA -dependent induction of OBP4 is associated with the reduced expression of RSL2 . Furthermore, ectopic expression of OBP4 or loss of RSL2 function results in ABA -insensitive root hair growth. Taken together, our results suggest that OBP4-mediated transcriptional repression of RSL2 contributes to the ABA -dependent inhibition of root hair growth in Arabidopsis.